Inflammatory response and oxidative stress in developing rat brain and its consequences on motor behavior following maternal administration of LPS and perinatal anoxia. Issue 8 (15th October 2013) - Stigger, Felipe; Lovatel, Gisele; Marques, Marília; Bertoldi, Karine; Moysés, Felipe; Elsner, Viviane; Siqueira, Ionara Rodrigues; Achaval, Matilde; Marcuzzo, Simone
Abstract: Cerebral palsy (CP) is a disorder of locomotion, posture and movement that can be caused by prenatal, perinatal or postnatal insults during brain development. An increased incidence of CP has been correlated to perinatal asphyxia and maternal infections during gestation. The effects of maternal exposure to low doses of bacterial endotoxin (lipopolysaccharide, LPS) associated or not with perinatal anoxia (PA) in oxidative and inflammatory parameters were examined in cerebral cortices of newborns pups. Concentrations of TNF‐α, IL‐1, IL‐4, SOD, CAT and DCF were measured by the ELISA method. Other newborn rats were assessed for neonatal developmental milestones from day 1 to 21. Motor behavior was also tested at P29 using open‐field and Rotarod. PA alone only increased IL‐1 expression in cerebral cortex with no changes in oxidative measures. PA also induced a slight impact on development and motor performance. LPS alone was not able to delay motor development but resulted in changes in motor activity and coordination with increased levels of IL‐1 and TNF‐α expression associated with a high production of free radicals and elevated SOD activity. When LPS and PA were combined, changes on inflammatory and oxidative stress parameters were greater. In addition, greater motor development and coordination impairments were observed. Prenatal exposure of pups to LPS appeared to sensitize the developing brain to effects of a subsequent anoxia insult resulting in an increased expression of pro‐inflammatory cytokines and increased free radical levels in the cerebral cortex. These outcomes suggest that oxidative and inflammatory parameters in the cerebral cortex are implicated in motor deficits following maternal infection and perinatal anoxia by acting in a synergistic manner during a critical period of development of the nervous system.